2012
DOI: 10.1021/ie202727r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Tetralin over Ir-Containing Mesoporous Catalysts

Abstract: A new series of catalysts based on noble metals have been prepared with the main aim of obtaining thiotolerant catalysts to be used in second-stage processes of mild hydrotreating. We studied the catalytic properties of 1 wt % Ir-containing mesoporous materials in the hydrogenation of tetralin to decalin, in the presence of 100 ppm of dibenzotiophene at 250 °C and 15 atm pressure of hydrogen, using a Parr reactor. Ir/mesoporous materials were prepared by wetness impregnation, using iridium acetylacetonate as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In previous works [14][15][16] we demonstrate that Ir-modified mesoporous materials possesses a kinetic constant one order of magnitude higher than commercial NiMo catalysts. The catalytic results revealed the good performance of these monometallic Irmodified catalysts at low temperatures, where high conversions and high yields of hydrogenation products were obtained, improving on the behavior displayed by the commercial catalyst.…”
Section: Introductionmentioning
confidence: 55%
“…In previous works [14][15][16] we demonstrate that Ir-modified mesoporous materials possesses a kinetic constant one order of magnitude higher than commercial NiMo catalysts. The catalytic results revealed the good performance of these monometallic Irmodified catalysts at low temperatures, where high conversions and high yields of hydrogenation products were obtained, improving on the behavior displayed by the commercial catalyst.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, NiMo and CoMo materials based on Nb-supported MCM-41 exhibited better performance in dibenzothiophene HDS . HDO of a lignin-derived phenolic compound such as 2,2′-biphenyl has been reported using a Ru/H-Beta catalyst to convert BCH. , cis / trans -Decahydronaphthalene was reported from above-indicated feedstocks using Pt-Pd/silica-alumina, Ir supported (SBA-16, SBA-3, and MCM-41), Ni/Al 2 O 3 , Ni 2 P/HPWSNS-0.13, Rh/Fe 2 O 3 -TiO 2 magnetic catalysts, Ni-Mo/γ-Al 2 O 3 , Ru/Al 2 O 3 and EAOAC ionic liquid/Ru-C + Hβ catalysts. Vijayakumar and Pandurangan reported that palladium-nickel impregnated on SBA-16 catalysts was effective for α-tetralone hydrodeoxygenation …”
Section: Introductionmentioning
confidence: 99%
“…The possible outcome of di-cyclohexyl methane (DCM), bi-cyclohexane (BCH), and decalin (DC) can be synthesized from different feedstocks such as 2-benzyl phenol, diphenyl ketone, , di-phenyl methane, 2-benzyl 4-ethyl phenol or 3-benzyl 4-ethyl phenol, benzofuran, benzyl phenyl ether, phenol with dibenzyl ether, and phenol with benzyl acetate for DCM; dibenzofuran, , dibenzothiophene, carbazole, cyclohexanone, biphenyl, 5,5′-biphenol, and phenol for BCH; and α-tetralone, tetralin, , naphthalene, α-naphthol, , and cyclopentanone for DC. The aforementioned feedstocks have been converted to jet-fuel range hydrocarbons through vapor phase and liquid phase catalytic reactions with various types of metal-containing catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In this arch for highly active and selective hydrotreatment catalysts for the oil industry, there are numerous works based on catalysts mainly with noble metals as active sites, since although they have a higher cost, the high conversions achieved justify their promising uses. Likewise, our previous works have shown that the acid support, the formation of bimetallic alloys, and the introduction of heteroatoms can greatly improve the performance of deposited metals in the active phase [10,11,12,13,14,15,16,17]. In this way of looking for more efficient catalysts, the supports with large surface areas have been greatly studied since they can achieve a great dispersion of the active phase, significantly improving the yield of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the support materials have been the protagonists of various studies. Among the most studied are metal oxides, such as Al 2 O 3 [4,5,6,7,8,9], and materials with different degrees of porosity, such as MCM (Mobil Composition of Matter), SBA, Santa Barbara Amorphous type material and zeolites [10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%